Legacy ebook - Messenger, Shannon (Keeper of the Lost Cities, 2019)
Illusions shatter—and Sophie and her friends face impossible choices—in this astonishing eighth book in the New York Times and USA TODAY bestselling Keeper of the Lost Cities series. Sophie Foster wants answers. But after a lifetime of lies, sometimes the truth is the most dangerous discovery. Even the smallest secret comes with terrifying new responsibilities. And Sophie's not the only one with blank spots in her past, or mysteries surrounding her family. She and her friends are part of something much bigger than they imagined—and their roles have already been chosen for them. Every clue drags them deeper into the conspiracy. Every memory forces them to question everything—especially one another. And the harder they fight, the more the lines blur between friend and enemy.